KONSUMSI PANGAN DAN SENG, SERTA DETERMINAN STATUS SENG IBU HAMIL DI KECAMATAN LEUWILIANG DAN CIBUNGBULANG, KABUPATEN BOGOR - Aslis Wirda Hayati; Hardinsyah Hardinsyah; Rimbawan Rimbawan (Media Gizi dan Keluarga, 2007)
ABSTRACT. The main objectives of this study were to analyze zinc status, nutrient dietary, quality zinc content, zinc intake, and determinant factor of zinc status. The research was based on previous study on "Effect of Multi-nutrients Fortified Food Supplementation for Pregnant Women and Child Growth and Development" and  some additional data of food  zinc content. Logistic regression was applied for determinants analysis. The results show that zinc serum level was 0.9±04mgll. The prevalence of zinc deficiency was 21.8%. Food intake ofpregnant women was very low (30.8% of suggested serving). Zinc content offood ranged from O.2mg (fried tempeh) to 22.9mg (local snail) per 100g oft he dried foods. Zinc intake was 6.3mglday, similar to 32.8% recommended dietary allowance (RDA). The subjects who have zinc intake lower than it's RDA (l9.3mglday) were 99.2%. The determinant ofzinc status was household income . Keywords: food consumption, zinc intake, zinc status, pregnant women,